2019
DOI: 10.7717/peerj.7742
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability evaluation and cultivar identification of tetraploid annual ryegrass using SSR markers

Abstract: Annual ryegrass (Lolium multiflorum) is a widely used cool-season turf and forage grass with high productivity and ornamental characteristics. However, the abundant intra-cultivar genetic variability usually hampers the application of conventional techniques for cultivar identification. The objectives of this study were to: (1) describe an efficient strategy for identification of six tetraploid annual ryegrass cultivars and (2) investigate the genetic diversity based on SSR markers. A total of 242 reliable ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…In contrast, high-resolution and high-throughput approach sequencing methods are more convenient and reliable for this task. In our previous study, SSR markers were used to distinguish 6 Italian ryegrass varieties [ 12 ]. We found that 17 out of 29 polymorphic SSR markers could not completely distinguish the 6 tested Italian ryegrass varieties.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, high-resolution and high-throughput approach sequencing methods are more convenient and reliable for this task. In our previous study, SSR markers were used to distinguish 6 Italian ryegrass varieties [ 12 ]. We found that 17 out of 29 polymorphic SSR markers could not completely distinguish the 6 tested Italian ryegrass varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional molecular markers are basically limited to dozens of pairs of primers, of which only a few hundred bands can be amplified based on PCR amplification [ 1 , 8 , 12 ]. In contrast, 18,558,247 SNP markers were detected in this study, which proves that RAD-seq could detect far more sites than traditional molecular markers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The markers associate with the non-repetitive regions of the genome and exhibit high mutation rates ( Kalia et al, 2011 ; Morgante, Hanafey & Powell, 2002 ). SSR markers have been widely used to evaluate the genetic variation for various plants, e.g., Medicago truncatula ( Eujayl et al, 2004 ), Lolium multiflorum ( Nie et al, 2019 ), Rhdodendron arboretum ( Sharma et al, 2020 ), Pteroceltis tatarinowii ( Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%